An Analysis of APP for Bonus Point Activity Service Based on Conjoint Model - Liang, Che-Pin; Chu, Li-Chuan (Archives of Business Research, 2018)
Information data application has given rise to significant changes in many industries, and convenience stores have also started to use APP software for the buns point activity in replacement of the original bonus point operation mode. The issue of how to attract more consumers to use APP for the bonus point activity is a very important research theme for managers of convenience stores. This paper first describes the development background and current situation of the bonus point activity. Next, the various factors and their attributes affecting consumers’ behavioral intention to choose to use APP for bonus point service are discussed by adopting conjoint analysis. Finally, management implications are proposed based on the research findings as references for convenience stores.